The Governance of Labour Administration : Reforms, Innovations and Challenges - Heyes, Jason; Rychly, Ludek; Heyes, Jason; Rychly, Ludek (Cheltenham, Gloucestershire, UK Edward Elgar Publishing)
Focusing on public administration activities in the field of national labour policy, this timely book provides detailed analyses of labour administration reforms, innovations and challenges in different countries, including detailed case studies from Brazil, Germany, India, Japan, South Africa, Sri Lanka and the US.
English
Keywords: KNXB; Employment Rights; Labour Administration; Labour Governance; Labour Inspection; Labour Ministries; Labour Policy; Public Administration; Social Dialogue